Adult education in relation to agricultural development : an evaluative study of a development block in Andhra Pradesh : report of a research project initiated by UNESCO - Sinha, Panday Rewati Raman, 1935- (National Institute of Community Development, 1974)
Study conducted in the Rajendranagar Community Development Block, Hyderabad District.